Inwestycje jako czynnik kształtowania ładu przestrzennego na przykładzie miasta Zamościa - Telega, Agnieszka; Telega, Ivan (Wyższa Szkoła Biznesu - National-Louis University w Nowym Sączu, 2009)
Management of the investment processes in the city should take into account the impact of these investments on spatial order of urban space. Deterioration of spatio-functional structure of the city and devastation of the cultural landscape significantly decreases the quality of life and adversely affects the competitiveness of the city. The purpose of this paper is an attempt to develop the model of spatial order and to assess influence of major investments in the city on selected areas of spatial order on the example of city of Zamoć. The study was limited to the investments incurred in the period of 1999-2008. The aim of following researches is to work out objective numeral measures of spatial order.
Investments as a factor influencing on the spatial order on the example of city of Zamość